Stakeholder views, financing and policy implications for reuse of wastewater for irrigation: a case from Hyderabad, India - Starkl, M.; Brunner, N.; Amerasinghe, Priyanie H.; Jampani, Mahesh; Kumar, D.; Asolekar, Shyam R.; Sonkamble, S.; Ahmed, S.; Wajihuddin, M.; Pratyusha, A.; Sarah, S. (MDPI, 2015)
When flowing through Hyderabad, the capital of Telangana, India, the Musi River picks up (partially) treated and untreated sewage from the city. Downstream of the city, farmers use this water for the irrigation of rice and vegetables. Treatment of the river water before it is used for irrigation would address the resulting risks for health and the environment. To keep the costs and operational efforts low for the farmers, the use of constructed wetlands is viewed as a suitable option. Towards this end, the paper investigates the interests and perceptions of government stakeholders and farmers on the treatment of wastewater for irrigation and further explores the consumer willingness to pay a higher price for cleaner produced vegetables. Full cost recovery from farmers and consumers cannot be expected, if mass scale treatment of irrigation water is implemented. Instead, both consumers and farmers would expect that the government supports treatment of irrigation water. Most stakeholders associated with the government weigh health and environment so high, that these criteria outweigh cost concerns. They also support the banning of irrigation with polluted water. However, fining farmers for using untreated river water would penalize them for pollution caused by others. Therefore public funding of irrigation water treatment is recommended.